2014
DOI: 10.1016/j.ijrobp.2013.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Radiation Therapy and Immunotherapy for Melanoma: A Review of Clinical Outcomes

Abstract: Radiotherapy has long played a role in the management of melanoma. Recent advances have also demonstrated the efficacy of immunotherapy in the treatment of melanoma. Preclinical data suggest a biologic interaction between radiotherapy and immunotherapy. Several clinical studies corroborate these findings. This review will summarize the outcomes of studies reporting on patients with melanoma treated with a combination of radiotherapy and immunotherapy. Vaccine therapies often use irradiated melanoma cells, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 79 publications
(80 reference statements)
1
94
0
1
Order By: Relevance
“…The RT was done both for palliation and for synergism with ipilimumab, as it could theoretically render the tumor more immunogenic. 14,15 She rapidly achieved a clinical response to vemurafenib (along with a pruritic rash requiring a dose reduction and a brief course of steroids). The patient developed fevers, chills and marked synovitis in a symmetric fashion, particularly in her wrists, hands and feet.…”
Section: Patientmentioning
confidence: 99%
“…The RT was done both for palliation and for synergism with ipilimumab, as it could theoretically render the tumor more immunogenic. 14,15 She rapidly achieved a clinical response to vemurafenib (along with a pruritic rash requiring a dose reduction and a brief course of steroids). The patient developed fevers, chills and marked synovitis in a symmetric fashion, particularly in her wrists, hands and feet.…”
Section: Patientmentioning
confidence: 99%
“…Several cases have recently been reported in which combi-nation therapy with immune-checkpoint inhibitors and radiotherapy malignant melanoma was successful [6]. An abscopal effect is known to manifest as a synergistic effect when using immune-checkpoint inhibitors in combination with radiation therapy [6] [7] [8].…”
Section: Resultsmentioning
confidence: 99%
“…The migration, invasion, conglutination and growth analyses of cancer cells are the most commonly used methods to judge cytoactivity. These methods can reflect the fact that the tumor leaves the primary tumor extracellular matrix (11)(12)(13)(14)(15). In the present study, it was found that the reproduction rate of the tumor cells was relatively low in the early passage.…”
Section: A B C D E F Discussionmentioning
confidence: 99%